Peluang dan Tantangan Indonesia Menuju Poros Maritim Dunia: Perspektif Politik Internasional - Fardhal Virgiawan Ramadhan; Ade Chaerul (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Indonesia has various benefits as a world maritime axis such as a large economic potential because Indonesia is the largest archipelagic country in the world, Indonesia has great economic potential in the maritime sector, including in the fields of fisheries, shipping and marine tourism. As the world's maritime axis, Indonesia must strengthen national security and defense as an archipelagic country, Indonesia has vast territorial waters, which need to be guarded against various threats, such as illegal fishing, ship theft, and terrorist activities at sea. The purpose of this research is to explain the world's maritime axis in an international political perspective. The research method used is qualitative research. The results of this study are that Indonesia has a very big opportunity to make itself the world's maritime axis. However, on the other hand, there are also several challenges that need to be overcome in developing Indonesia's maritime sector. Opportunities that exist include enormous maritime potential, strategic geographical position, the existence of international shipping lanes, and attractive maritime tourism potential. While the challenges faced are the lack of adequate infrastructure and technology, limited competent human resources, maritime security issues, and the lack of appropriate policies in regulating the maritime sector.